Pengaruh Non Perfoaming Loan (NPL), Loan to Deposit Ratio (LDR), Biaya Operasional Pendapatan Operasional (BOPO) Terhadap Profitabilitas Perbankan Syariah Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2019-2021 - Yenni Yunianingsih (LPPM STIKes SITI HAJAR dan Insight Power, 2023)
A country's economic development is a requirement to achieve people's welfare. The process involves many parties where each party integrates and interacts with each other to create national economic goals. The function of the bank is very important for the economy of a country because the bank acts as a financial intermediary and facilitates the flow of payment traffic. One of the parties involved in economic development is banking financial institutions. The research aims at the effect of non-performing loans (NPL), loan-to-deposit ratio (LDR), and operational income operating costs (BOPO) on the profitability (ROA) of Islamic banking listed on the Indonesian stock exchange for the 2019-2021 period. The method used is a quantitative approach. The results showed that NPL had a significance value of 0.006<0.05, it could be concluded that NPL had an effect on ROA, LDR had a significance value of 0.005<0.05, it could be concluded that LDR had an effect on ROA and BOPO had a significance value of 0.003<0.05, it could be concluded that BOPO has an effect on ROA.Keywords: Nonperformingg loan (NPL), Loan to deposit ratio (LDR), Operating income operating costs (BOPO), Profitability (ROA)